Powerpoint-Based Interactive Media Development in Online Learning - Raudatul Izmi; Utari; Mia Andriyani (PT. Mifandi Mandiri Digital, 2022)
When the COVID-19 pandemic hit almost all countries, all activities were limited and it was recommended to stay indoors, including the online learning process. This research is based on problems that occur in the learning process during the Covid-19 pandemic. Overcome this problem, it can be done using interactive media. This study aims to determine the development of technology in the world of education. One of them is interactive media-based learning media. In learning media, interactive media can be further developed to be varied so that the function of the media becomes wider. The development of media is not easy, but the need for an effort to maximize it. Therefore, the use of media is very important to improve and support the delivery of material. Interactive media usually refers to a computer system service that responds to actions between users in presenting material, such as text, images, animation, video, and audio.